AB0068 Hypoxia and rheumatoid phenotype decrease the capacity of synovial fibroblasts to suppress t helper cell proliferation through ido1-mediated tryptophan catabolism. (15th June 2017) - Tykocinski, L-O; Kaul, N-C; Adam, I; Mohapatra, SR; Krienke, S; Opitz, CA; Lorenz, H-M
Abstract : Background: The pathogenesis of rheumatoid arthritis (RA) is linked to functional changes in synovial fibroblasts (SF) and local infiltration of T lymphocytes. Increased synovial inflammation is also associated with a hypoxic joint microenvironment. Oxygen levels in the joints of RA patients are significantly decreased compared to those of osteoarthritis (OA) patients with values of about 22.5mmHg corresponding to ambient oxygen tensions of 3.2%. So far, little is known about the effects of hypoxia on the interaction between fibroblasts and T lymphocytes and its implications on the pathophysiology of RA. Objectives: The aim of this study was to compare the influence of SF from RA versus OA patients on T helper (Th) cell responses both under normoxic and hypoxic conditions. Methods: SF were isolated from synovectomy tissues of OA or RA patients, Th cells were isolated from peripheral blood of RA patients or healthy donors. Cell cultures were performed under normoxic or hypoxic (3% O2 ) conditions. Th cell proliferation was determined by PKH26 labelling and flow cytometry. Cytokine secretion was quantified by ELISA. Indoleamine 2, 3-dioxygenase 1 (IDO1) expression was analysed by Western Blot and expression of enzymes of the kynurenine pathway by real-time PCR. Tryptophan/ kynurenine levels in culture supernatants were quantified by HPLC. Results: SF strongly inhibited the proliferation of co-cultured Th cells. Tryptophan was completely depleted within a few days in co-cultures of SF and Th cells, resulting in eukaryotic initiation factor (eIF)2α phosphorylation, TCRζ-chain down-regulation and proliferation arrest. Blocking of IDO1 completely restored Th cell proliferation, indicating that SF suppressed the proliferation of Th cells through IDO1-mediated tryptophan catabolism. Interestingly, RASF showed a significantly lower IDO1 expression, tryptophan metabolism and a weaker Th cell suppressive capacity compared to OASF. Under hypoxic conditions, the secretion of IFNg, the expression of IDO1, the tryptophan metabolism and the Th cell suppressive capacity of both OASF and RASF were significantly reduced. Conclusions: SF suppressed Th cell growth through IDO1-mediated tryptophan catabolism. This mechanism may play an important role in preventing inappropriate Th cell responses under normal conditions. The reduced tryptophan metabolism under hypoxia together with the inferior efficiency of RASF to restrict T cell proliferation likely supports the development of synovitis in RA. Disclosure of Interest: None declared